On Close to Scalar Families for Fractional Evolution Equations: Zero–One Law - Lizama-Yanez, C (Springer New York LLC, 2019)
For {Rα,β(t)}t≥0 being a strongly continuous (α, β) -resolvent family on a Banach space, we show that the assumption supt>0‖1tβ-1Eα,β(λtα)Rα,β(t)-I‖=:θ<1 yields that Rα , β(t) = tβ - 1Eα , β(λtα) for all t> 0 and λ≥ 0 , where Eα , β(s) denotes the Mittag–Leffler function with parameters α, β> 0. This implication is known as the zero–one law. In particular, we provide new insights on the structural properties of the theories of C-semigroups, strongly continuous cosine families, β-times integrated semigroups and α-resolvent families, among others. For β-times integrated semigroups, an example shows that in the sector {(α,β):0<α≤1;α≤β} the requirement θ< 1 is optimal: for θ= 1 the result is false. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.